Distributed Ultra-Precise Time-Synchronization with Minimized Synchronization Data Traffic - Klob, Sebastian; Maul, Thomas; Robert, Joerg (Proceedings of the 2024 14th International Conference on Indoor Positioning and Indoor Navigation, IPIN 2024, 2024)
Most modern systems require some form precise time and frequency synchronization, and the demand for more precise solutions is further increasing. Smart manufacturing will likely incorporate wireless sensor networks in the future to serve various purposes, such as sensing, localization, and communication. Managing a variety of tasks within such a network necessitates synchronization to enhance efficiency. Additionally, runtime-based localization schemes, such as Time Difference of Arrival (TDoA), rely heavily on precise time synchronization for their accuracy. This paper proposes an extension of a synchronization scheme using so-called Signals of Opportunity (SoO). Currently, a significant amount of data must be exchanged between the base stations in a network to achieve precise synchronization. For reducing the required data rates, our proposed system utilizes only the outer frequencies of the SoO for synchronization. We demonstrate that using only parts of the bandwidth still results in precise estimates for time and frequency errors. Additionally, we present measurement results for the proposed scheme and confirm that the synchronization precision remains high, despite the omission of large portions of the SoO.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Cloud RAN; IoT; Localization; LPWAN; Software Defined Radio; Synchronization